(untitled) (DARYAFT, 2022)
If review is conducted on the research and criticism done on the words and vocabulary used by Iqbal, then it seems apparent that it is fermentation of Arab, Ajmi and Hindu Islamic civilization. However, the influence of Arabic and Islamic civilization prevails. If we study the core of the words used by Iqbal in his works, then we can trace the true meaning behind them. When Iqbal embraces a word, he makes it, and its several possible meanings, part of the text. The function of verb in any poets writing reflects the connection between the word and the poets’ life. This is also seen in the case of Iqbal who uses these functions frequently. Iqal uses more than one verb in his verses with multiple figurative meanings. The use of figurative language is also an interesting aspect of Iqbal’s writing. Moreover, Iqbal explores the spiritual meaning of the words. In this article, special attention will be given to Iqbal’s use of words and their multiple figurative meanings.